Ответы и объяснения

2014-04-06T20:26:15+04:00
(х²+2х-3)/(х²+3х-10):(х²+7х+12)/(х²-9х+14)=(х+3)(х-1)/(х+5)(х-2):(х+4)(х+3)/(х-2)(х-7)=
(х+3)(х-1)(х-2)(х-7):(х+5)(х-2)(х+4)(х+3)=(х-1)(х-7):(х+5)(х+4)=(х²-8х+7)/(х²+9х+20)

1x2 + 2x - 3 = 0
D = b2 - 4ac = 22 - 4∙1∙(-3) = 16
D > 0 ⇒ уравнение имеет 2 корня

x = -b ± √D / 2a
x1 = (-2 - √16) / (2∙1) = -3
x2 = (-2 + √16) / (2∙1) = 1

Ответ: x = -3; 1

1x2 + 3x - 10 = 0
D = b2 - 4ac = 32 - 4∙1∙(-10) = 49
D > 0 ⇒ уравнение имеет 2 корня

x = -b ± √D / 2a
x1 = (-3 - √49) / (2∙1) = -5
x2 = (-3 + √49) / (2∙1) = 2

Ответ: x = -5; 2

1x2 + 7x + 12 = 0
D = b2 - 4ac = 72 - 4∙1∙12 = 1
D > 0 ⇒ уравнение имеет 2 корня

x = -b ± √D / 2a
x1 = (-7 - √1) / (2∙1) = -4
x2 = (-7 + √1) / (2∙1) = -3

Ответ: x = -4; -3
1x2 - 9x + 14 = 0
D = b2 - 4ac = (-9)2 - 4∙1∙14 = 25
D > 0 ⇒ уравнение имеет 2 корня

x = -b ± √D / 2a
x1 = (9 - √25) / (2∙1) = 2
x2 = (9 + √25) / (2∙1) = 7

Ответ: x = 2; 7